Conversion to or within Islam in Some Aljamiado Exhortatory Texts: “Fízose creyente […] i fue buena su creyencia con Allah” - Olivier Brisville-Fertin (Al-Qantara : Revista de Estudios Arabes, 2024)
This article explores the motif of inter- and intra-religious conversion in Aljamiado texts, focusing particularly on the functions and motivations behind its use in preaching. A review of some known apologetic and doctrinal texts highlights that conversion narratives were suitable for religious instruction, thus demonstrating a pragmatic flexibility between textual genre and discursive use. The analysis of three episodes in unpublished admonitions underscores their rhetorical role as exempla to persuade their audience: these episodes illustrate the theme of exhortations, provide models of piety—especially of repentance or obedience—, and reaffirm the supremacy of Islam over other religions. The analysis of an early-Christian conversion story inserted into an Islamic exegetical session allows for a deeper understanding of its significance and the echoes it may have had in the Morisco context of copying and reading: by refuting idolatry, this Islamised Christian narrative condemned Catholic dulia; by demonstrating a case of confessional concealment, it legitimised Morisco dissimulation; recalling the reward of religious martyrdom and Allah’s eventual chastisement of unbelievers, it also provided comfort and fostered the congregation’s fortitude and forbearance. A transliteration of this unpublished exegetical session is provided in the annex.